2023
DOI: 10.3390/ijms241411274
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Mechanism of Phenazine-1-Carboxylic Acid against Pestalotiopsis kenyana

Abstract: Pestalotiopsis sp. is an important class of plant pathogenic fungi that can infect a variety of crops. We have proved the pathogenicity of P. kenyana on bayberry leaves and caused bayberry blight. Phenazine-1-carboxylic acid (PCA) has the characteristics of high efficiency, low toxicity, and environmental friendliness, which can prevent fungal diseases on a variety of crops. In this study, the effect of PCA on the morphological, physiological, and molecular characteristics of P. kenyana has been investigated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Electron microscopic analysis of PCA against Botrytis cinerea revealed mycelial withering with edge burrs, rupturing of vacuoles, and distorted structure of various organelles ( Zhang et al, 2015 ). In a phenazine-1-carboxylic acid treatment of Pestalotiopsis kenyana phytopathogenic fungus, damage of cell membranes and mycelial formation, reduced mitochondrial membrane potential, and increased ROS levels were observed ( Xun et al, 2023 ). A phenazine compound was obtained from Lactococcus spp.…”
Section: Biological Control Of Fusaria By Lactic Acid Bacteriamentioning
confidence: 99%
“…Electron microscopic analysis of PCA against Botrytis cinerea revealed mycelial withering with edge burrs, rupturing of vacuoles, and distorted structure of various organelles ( Zhang et al, 2015 ). In a phenazine-1-carboxylic acid treatment of Pestalotiopsis kenyana phytopathogenic fungus, damage of cell membranes and mycelial formation, reduced mitochondrial membrane potential, and increased ROS levels were observed ( Xun et al, 2023 ). A phenazine compound was obtained from Lactococcus spp.…”
Section: Biological Control Of Fusaria By Lactic Acid Bacteriamentioning
confidence: 99%
“…To explore the interaction between SCBZSX5 and sorghum-sudangrass hybrids, we analyzed the whole metabolome between infected sorghum-sudangrass hybrids and healthy plants [13]. The PCA score map (Figure 10a) showed that the PC1 and PC2 accounted for 58.42% and 30.24% of the total variance, respectively, indicating that there were significant differences in the metabolic profiles of different groups of samples.…”
Section: Effect Of Pathogenic Fungi On Plant Metabolismmentioning
confidence: 99%